Spatial planning in the big data revolution - Voghera, Angioletta; La Riccia, Luigi 1977- (IGI Global, 2019)
"This book explores in a systematic way the themes of big data and the spatial analysis, with theoretical and operative recommendations for urban planning. It also brings together different work methodologies that combine the potential of large data analysis with GIS applications in dedicated tools specifically for sectoral, territorial, environmental, transport, energy, real estate and landscape assessment"...
Includes bibliographical references and index
Keywords: Public spaces -- Planning -- Data processing; City planning -- Data processing; Geographic information systems; Big data; Geoinformationssystem; Stadtplanung; Aufsatzsammlung